Blood Meal Identification in Field-Captured Sand flies: Comparison of PCR-RFLP and ELISA Assays - N Maleki-Ravasan; MA Oshaghi; E Javadian; Y Rassi; J Sadraei; F Mohtarami (Tehran University of Medical Sciences, 2009)
Background: We aimed to develop a PCR-RFLP assay based on available sequences of putative vertebrate hosts to identify blood meals ingested by field female sand fly in the northwest of Iran. In addition, the utility of PCR-RFLP was compared with ELISA as a standard method. Methods: This experimental study was performed in the Insect Molecular Biology Laboratory of School of Public Health, Tehran University of Medical Sciences, Iran in 2006-2007. For PCR-RFLP a set of conserved vertebrate primers were used to amplify a part of the host mitochondrial cytochrome b (cyt b) gene followed by digestion of the PCR products by Hae III enzyme. Results: The PCR-RFLP and ELISA assays revealed that 34% and 27% of field-collected sand flies had fed on humans, respectively. Additionally, PCR-RFLP assays could reveal specific host DNA as well as the components of mixed blood meals. Results of PCR-RFLP assay showed that the sand flies had fed on cow (54%), human (10%), dog (4%), human and cow (21%), dog and cow (14%), and human and dog (3%). Conclusion: The results can provide a novel method for rapid diagnosis of blood meal taken by sandflies. The advantages and limitations of PCR and ELISA assays are discussed.